Effectiveness of high-flow nasal cannula versus noninvasive ventilation and conventional oxygen therapy in patients weaned from invasive mechanical ventilation - Amira Ahmed Ahmed Mahmoud Elghonemy; Emad Korraa; Rehab M. Mohammed (The Egyptian Journal of Bronchology)
Abstract Background Reintubation after liberation from mechanical ventilation is a common adverse event observed in the intensive care unit (ICU) with significant implications for patient outcomes. Sequential oxygen therapies, including noninvasive ventilation (NIV) and high-flow nasal cannula (HFNC) in addition to the conventional oxygen therapy (COT), are commonly employed in the post-extubation setting to lessen reintubation risk, but their comparative efficacy remains controversial. Objective To compare the efficacy of NIV, HFNC, and COT as post-extubation respiratory support. Methods A prospective, randomized, clinical, parallel-group study enrolled extubated patients who were randomized and assigned to receive either NIV support or HFNC or COT. Primary outcomes included reintubation rates while secondary outcomes included post-extubation hemodynamics and arterial blood gases (ABGs), ICU length of stay, and ICU mortality. Results Sixty patients were recruited and equally randomized into the three groups (20 per group). The NIV and HFNC groups had lower reintubation rates [9/20 (45%), 12/20 (60%), respectively] compared to the COT group (15/20, 75%), yet with insignificant difference between the three groups (p > 0.05). The relative risk (RR) and 95% confidence interval (CI) of reintubation were insignificantly lower in the NIV group [RR, 0.600; 95% CI 0.347–1.036, p = 0.067], and to a lesser extent in the HFNC group [RR, 0.800; 95% CI 0.516–1.240, p = 0.318] compared to the COT group, while RR between NIV and HFNC groups was 0.750; 95% CI 0.411–1.370; p = 0.350. The NIV and HFNC groups had similar, significantly shorter ICU length of stay compared to the COT group (p < 0.001). ICU mortality was lowest in the NIV group (8/20, 40%), followed by the HFNC (13/20, 65%) and highest in the COT group (15/20, 75%) with significant difference between the NIV and COT groups [RR, 0.53; 95% CI 0.29–0.96, p = 0.037]. Conclusion The study findings suggest comparable efficacy of NIV, HFNC, and COT devices in preventing reintubation within 48 h post-extubation, and NIV displayed some advantages over HFNC and COT in terms of lower reintubation and mortality rates. Trial registration ClinicalTrials.gov, NCT06593509 . Registered 17 August 2024—retrospectively registered.